2019
DOI: 10.1002/ps.5519
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐Seq identification of candidate defense genes by analyzing Mythimna separata feeding‐damage induced systemic resistance in balsas teosinte

Abstract: BACKGROUND Armyworm (Mythimna separata) is a destructive herbivore for maize. Balsas teosinte (Zea mays ssp. parviglumis), the direct wild ancestor of cultivated maize, has shown great potential to defend against herbivory. Here, based on armyworm bioassay, we compared responses of teosinte and B73 maize inbred during armyworm attack in their transcriptome profiles to elucidate the gene expression changes involved in teosinte responses to armyworm attack. The goal of this study was to identify novel resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Additionally, AMP and JAC1 , two maize genes that are up‐regulated in response to S. frugiperda feeding (Figure S2 ), reduced caterpillar weight gain when overexpressed in maize. Although transcriptomic studies have identified numerous maize genes that are up‐regulated in response to arthropod feeding (Bui et al ., 2018 ; Guo et al ., 2019 ; Pan et al ., 2020 ; Song et al ., 2017 ; Tzin et al ., 2015 , 2017 ; Wang et al ., 2017 ; Yang et al ., 2020 ; Zhang et al ., 2016 ), the majority of these genes have not been investigated for their roles in plant defence against herbivory. This is at least in part due to the time and cost of creating maize lines that have individual genes overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AMP and JAC1 , two maize genes that are up‐regulated in response to S. frugiperda feeding (Figure S2 ), reduced caterpillar weight gain when overexpressed in maize. Although transcriptomic studies have identified numerous maize genes that are up‐regulated in response to arthropod feeding (Bui et al ., 2018 ; Guo et al ., 2019 ; Pan et al ., 2020 ; Song et al ., 2017 ; Tzin et al ., 2015 , 2017 ; Wang et al ., 2017 ; Yang et al ., 2020 ; Zhang et al ., 2016 ), the majority of these genes have not been investigated for their roles in plant defence against herbivory. This is at least in part due to the time and cost of creating maize lines that have individual genes overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of selected reference genes. JA and SA signaling pathways play key roles in plant defense against herbivorous insects 51,52 , and JA and SA responsive genes could be expressed upon herbivore attack or hormone stimuli 51,53 . A key transcription factor of JA signaling-CsMYC2, a key enzyme in the biosynthesis of JA-CsOPR3, two enzyme involved in the biosynthesis of SA-CsPAL and CsPALc were selected as target genes to validate the rationality of diurnal expression in different tissues, JA treatment and E. onukii infestation, T. aurantii infestation or E. obliqua regurgitant treatment individually.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Additionally, AMP and JAC1, two maize genes that are upregulated in response to S. frugiperda feeding ( Figure S1), reduced caterpillar weight gain when overexpressed in maize. Although transcriptomic studies have identified numerous maize genes that are upregulated in response to arthropod feeding (Bui et al, 2018;Pan et al, 2020;Tzin et al, 2015Tzin et al, , 2017Yang et al, 2020;Guo et al, 2019;Song et al, 2017;Wang et al, 2017;Zhang et al, 2016), the majority of these genes have not been investigated for their role in plant defense against herbivory. This is at least in part due to the time and cost of creating maize lines that have individual genes overexpressed.…”
Section: Discussionmentioning
confidence: 99%